Design and Testing of Brushless DC Motor Components of A6 Steel Additively Manufactured by Selective Laser Sintering - Zaharia, Sebastian-Marian; Pop, Mihai Alin; Buican, George Razvan; Chicos, Lucia-Antoneta; Stamate, Valentin Marian; Pascariu, Ionut Stelian; Lancea, Camil (MDPI AG, 2023)
Metallic additive manufacturing technology is seeing increasing use from aviation companies manufacturing prototypes or components with complex geometric shapes, which are then tested and put into operation. This paper presents the design, fabrication via a selective laser sintering process, and testing of the mechanical performance by performing three-point bending and tensile tests on A6 steel specimens. After performing the mechanical tests on specimens made from A6 steel manufactured via the SLS process, the following performances were obtained: the maximum three-point bending strength was 983.6 MPa and the maximum tensile strength was 398.6 MPa. In the microscopic analysis of the specimens manufactured by the selective laser sintering process, a homogeneous structure with defects specific to additive processes (voids) was revealed. Additionally, the feasibility of designing, manufacturing through the selective laser sintering process and subsequent testing of some components (rotor, right case, left case and motor mount) from a brushless motor made from A6 steel material was demonstrated. After testing the brushless motor, the main performances showed stable behavior of the motor and a linear dependence with the increase in electronic speed control signal or motor electrical speed, resulting in a maximum thrust force of 4.68 kgf at 7800 RPM.
Keywords: brushless motor; performance analysis; selective laser sintering; mechanical testing